Productivity and improvement approach in industrial engineering of San Marcos University. Exploratory study oriented to world-class competitiveness - Acevedo Borrego, Adolfo Oswaldo (2017)
In order to best results in performance, industrial engineer considers the process management, human resources and seeking productivity and efficiency, also managing opportunities, the first focuses on the system in balance and operating materials, the second it is the development of tools and techniques of continuous improvement that characterizes the profession. The aim is to show the propensity of the industrial engineer to stability and productivity or to change and improvement. The method is exploratory research with academic proposals documentary analysis questionnaire to define the educational emphasis, inferential statistics is applied in a sample of undergraduate and graduate to corroborate the hypothesis. In the results the training balance considering the development of skills against global competition, and the need for an academic project to expand a vision and projecting from a mission that emphasizes the formation of industrial engineer competitive and world-class.